Lakonizmus Csehov prózájában és a magyar fordításban: (A kutyás hölgy interpretációjához) - Zoltán, Dominika (Studia Litteraria, 2020)
The paper exemplifies how important translation analysis can be to interpret even the original work. It focuses on a certain text, the Hungarian – and in some cases the English, German and Polish – translation of the well-known Chekhov short story, "The Lady with the Dog”, to comprehensively illustrate the different translational solutions, and as a consequence it gets closer to the interpretation of the nature of Chekhov’s laconism, parabolic writing method.